Removing Barriers to Public Transport Fare Integration in Poland : Key Directions of Change - World Bank (World Bank, Washington, DC, 2016)
The need for more sustainable and integrative planning processes as a way of dealing with the complexity of urban mobility has been widely recognized. Within the European Union (EU) there has been an enhanced focus on urban mobility solutions where local authorities move away from past ‘silo approaches’ and develop approaches that can stimulate a shift towards cleaner and more sustainable transport modes, in line with the EU’s 2013 Urban Mobility Package and Sustainable Urban Mobility Plans (SUMPs).As people choose to move away from cities to the periphery or to neighboring municipalities, it becomes critical that the organization of urban transport services, including commuter rail, is coordinated within functional urban areas based on travel-to-work patterns and not be limited to a city’s administrative area.International experience suggests that public transport planners must recognize two integration dimensions: (a) integration among all modes and routes comprising the multi-modal public transport network, (b) integration of the public transport offer within a functional urban area, such that the public transport offer matches the mobility requirements of passengers. Successful integration in both dimensions will provide a more customer-friendly experience and make public transport more efficient and cost-effective.The objective of this Report is to assess barriers to fare integration and impediments to integrated service planning. More specifically, it aims to: analyze the current legal framework, review current fare discount policy and public financing of such discounts, identify legal obstacles to fare integration; present examples of European best practice in the area of public transport integration; and provide recommendations to remove barriers to fare and ticketing integration.The World Bank identified six key recommendations aimed at incentivizing public transport integration: i) Introducing uniform statutory fare discount system. ii) Reforming the system for financing statutory fare discounts. iii) Removing barriers to cooperation among different levels of self-government. iv) Strengthening local authorities responsible for transport and creating open integration platforms. v) Protecting PSO Operators from creaming skimming. vi)Promote fare integration. Changing the status quo will require significant changes to the legal environment for public transport aimed at removing barriers to integration.